2010
DOI: 10.1007/s11581-010-0420-7
|View full text |Cite
|
Sign up to set email alerts
|

Ionic conductivity studies on LiSmO2 by impedance spectroscopy

Abstract: Lithium samarium oxide has been prepared by solid-state reaction method and characterized by X-ray diffraction (XRD) and impedance spectroscopy. XRD pattern of the sample reveals the formation of the sample. The conductivity studies, dielectric studies, and modulus analysis of the samples have been carried out for different temperatures. The bulk conductivity of the sample has been found to be 1.21×10 −5 Scm −1 at 420°C. The temperature variation of the direct current conductivity obeys the Arrhenius relation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…According to the XRD patterns (Figure ), when the amount of Sm 2 O 3 reaches 0.4 wt%, some unknown diffraction peaks have been detected and their intensities increase by the amount of used Sm 2 O 3 . Compared with the PDF files of X'Pert High Score software, these XRD peaks can be matched to the crystalline phase of SmLiO 2 (JCPDS 01‐073‐1061) which this phase has a low melting point of about 1000°C …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the XRD patterns (Figure ), when the amount of Sm 2 O 3 reaches 0.4 wt%, some unknown diffraction peaks have been detected and their intensities increase by the amount of used Sm 2 O 3 . Compared with the PDF files of X'Pert High Score software, these XRD peaks can be matched to the crystalline phase of SmLiO 2 (JCPDS 01‐073‐1061) which this phase has a low melting point of about 1000°C …”
Section: Resultsmentioning
confidence: 99%
“…Compared with the PDF files of X'Pert High Score software, these XRD peaks can be matched to the crystalline phase of SmLiO 2 (JCPDS 01-073-1061) which this phase has a low melting point of about 1000°C. 24 The relationship between lattice parameters and Sm 2 O 3 content is shown in Figure 3. Both the a and the c lattice constants of samples increase with increasing Sm 2 O 3 concentration when Sm 2 O 3 content is higher than 0.2 wt%; the parameters remain almost constant with continued addition.…”
Section: Characterization Techniquesmentioning
confidence: 99%
“…The electrode effect usually appears at the relatively low-frequency end. It is a typical effect of an ionic conductor and it suggested that the mobile charge carriers are ions which are blocking the metal-sample interface [19][20][21]. The presence or absence of an electrode features provides an indication as to whether ionic conductivity is present.…”
Section: Resultsmentioning
confidence: 99%
“…It is observed that the idealized impedance plane plots of Z ‫||‬ as a function of Z ‫|‬ , i.e. Cole -Cole plots of the films (Z ‫|‬ and Z ‫||‬ denote the real and imaginary parts of the complex impedance Z*), contain a semi circular arc and inclined spike, both of which are characteristic behaviour of ionic conductivity of solids with blocking electrodes [24]. The semicircle indicates the parallel combination of bulk resistance (due to the migration of ions) and bulk capacitance (due to the immobile polymer chains).…”
Section: Ftir Studiesmentioning
confidence: 99%